CHARACTERIZATION AND RECOVERY OF BIOACTIVE COMPOUNDS FROM NATURAL SOURCES AND BY-PRODUCTS - Gaglianò, Martina; Cipparrone, Gabriella; De Luca, Giuseppina; Cassano, Alfredo (Università della Calabria, 2024)
The work presented in this PhD thesis aims to chemically characterize natural sources and by-products to properly design integrated systems to recover and fractionate bioactive compounds, such as polyphenols. Various analytical techniques, including UV-visible spectrophotometry, High-Performance Liquid Chromatography (HPLC), Mass Spectrometry (MS), and especially Nuclear Magnetic Resonance (NMR) coupled with chemometric methods, were employed to study the metabolomic profile of the investigated matrices. On the other hand, membrane technologies such as ultrafiltration (UF) and nanofiltration (NF) as well as polymeric resins were applied over conventional technologies for extracting and separating valuable molecules. The work, supported by the University of Calabria and POR Calabria 4 FSE/FESR 201432020, was developed within the Department of Chemical and Chemical Technologies (CTC) of the University of Calabria (Italy). Part of the experimental work was carried out at the Institute on Membrane Technology (ITM) of Italian National Research Council (CNR), located in Rende (CS, Italy). An almost six-months stage was also performed at the Institute of Food Engineering for Development (IIAD) of the Universitat Politècnica de València (UPV). Chapter 1 of this thesis briefly introduces theoretical concepts about characterisation and separation techniques, while the following Chapters show the experimental results of the conducted research. The first work, presented in Chapter 2, deals with the characterization of Calabrian apple juices from different cultivars (Pink Lady,Golden Delicious, Fuji, and Royal Gala) by NMR and HPLC-UV-ESI-MS/MS methodologies. Specifically, the combined use of 1H-NMR spectra and the multivariate analysis, particularly PrincipComponent Analysis (PCA) was tested to evaluate the possibility of distinguishing juices depending on the variety. Moreover, a nanofiltration (NF) process was applied to the Golden Delicious juice to produce enriched fractions in phenolic compounds. However, the composition of apple juice is complex, with valuable compounds having similar molecular masses to sugars, resulting in insufficient NF membrane selectivity. Therefore, in a subsequent work, NF membranes with a molecular weight cut-off (MWCO) ranging from 200 to 600 Da were tested to reduce the sugar content in apple juice through a combination of diafiltration and batch concentration processes. Membrane technologies such as UF and NF were also applied for the recovery of bioactive compounds from citrus tacle juice. In this third study, spectrophotometric assays and 1HNMR spectra of fractions coming from membrane operations coupled with the Principal Component Analysis (PCA), were used to explore the impact of UF and NF processes on the metabolic profile of the juice. In the fourth work NMR spectroscopy was applied to analyze extracts from the seeds and inflorescences of different varieties of Cannabis sativa grown in Calabria. Finally, the last study focuses on the recovery and purification of bioactive compounds from white wine lees, a by-product of the wine processing industry, through the use of different commercial nonionic resins.
Università della Calabria Dipartimento di Fisica Dottorato di Ricerca in Scienze e Tecnologie Fisiche, Chimiche e dei Materiali CICLO XXVI
Keywords: NMR. HPLC-UV-MS. Estratti naturali. Operazioni a membranaa